Influence of discrimination perception on career exploration of higher vocational students: Chain mediating effect test - Liu, Xuejun; Sun, Xianjun; Hao, Qin (Frontiers in Psychology, 2022)
The transformation of vocational education from "level" to "type" has been an important logic thread of Chinese vocational education reform since the 21st century. This study investigates the influence of discrimination perception on career exploration of higher vocational students, and provides an empirical basis for the reform and development of typology in Chinese vocational institutions.Using the questionnaire survey method, 893 higher vocational students from four higher vocational colleges in Jiangsu Province were investigated by using the Discrimination Perception Scale, the Core Self-Evaluation Scale, the Chinese version of the Acceptance and Action Questionnaire, the Chinese version of the Cognitive Fusion Questionnaire and the Career Exploration Scale. The data were analyzed using SPSS26.0 and Amos23.0, and the results showed that discrimination perception was significantly negatively correlated with core self-evaluation, psychological flexibility and career exploration (r=-0.487, -0.497, -0.326, P<0.01), core self-evaluation was significantly positively correlated with psychological flexibility and career exploration (r=0.518,0.352, P <0.01), and psychological flexibility was significantly positively correlated with career exploration (r=0.386, P<0.01); core self-evaluation and psychological flexibility mediated the effect between discrimination perception and career exploration with effect sizes of -0.054 and -0.061, respectively; core self-evaluation and psychological flexibility mediated the chain effect between discrimination perception and career exploration of higher vocational students with effect sizes of - 0.030. Therefore, discrimination perception not only directly influences career exploration of higher vocational students, but also indirectly influences career exploration of higher vocational students through the separate mediating effects of core self-evaluation and psychological flexibility and the chain mediating effects of core self-evaluation and psychological flexibility. Accordingly, it is proposed that we should continue to vigorously promote the typology of vocational institutions, strengthen the quality improvement of vocational institutions and improve the image of vocational institutions, and pay attention to the cultivation of core self-evaluation and psychological flexibility of higher vocational students.